2021
DOI: 10.2174/1570162x19666210614124543
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic Hormone-Independent Cushing Syndrome with Right Adrenal Adenoma and HIV Infection: A Case Report

Abstract: Background: Adrenocorticotropic hormone (ACTH)-independent Cushing's syndrome (CS) with right adrenal adenoma combined with HIV infection has rarely been reported. Case presentation: A 39-year-old Chinese male patient with HIV infection was admitted to our hospital due to increased blood pressure in the previous 2 years and weight gain in the previous 6 months. Endocrinological examinations showed that blood cortisol (8 a.m.) was 22.23 µg/dl, the level of ACTH (8 a.m.) was less than 1pg/ml and twenty-four-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Clinical manifestations of PBMAH include weight gain, impaired glucose tolerance or diabetes mellitus, hypertension, osteoporosis and hypokalemia. Our research showed that 83.3% (25/30) patients have clinical symptoms of CS, similar to the research summarized by Duan (86.7%, 26/30) 28 , but significantly higher than in the research by Libé (31.3%, 10/32) 29 , this may be associated with the elevated UFC/24 h levels in most patients 28 . In these cases, hypertension was the most common clinical manifestation (93.3%), others include weight gain (63.3%), osteoporosis (50%), diabetes (50%) and hypokalemia (70%).…”
Section: Discussionsupporting
confidence: 89%
“…Clinical manifestations of PBMAH include weight gain, impaired glucose tolerance or diabetes mellitus, hypertension, osteoporosis and hypokalemia. Our research showed that 83.3% (25/30) patients have clinical symptoms of CS, similar to the research summarized by Duan (86.7%, 26/30) 28 , but significantly higher than in the research by Libé (31.3%, 10/32) 29 , this may be associated with the elevated UFC/24 h levels in most patients 28 . In these cases, hypertension was the most common clinical manifestation (93.3%), others include weight gain (63.3%), osteoporosis (50%), diabetes (50%) and hypokalemia (70%).…”
Section: Discussionsupporting
confidence: 89%